Documentation and description of sounds and grammar of Higaonon spoken in Opol, Misamis Oriental - Abingosa, Danilyn Tayag; Pasandalan, Sittie Noffaisah; Alovera, Jay Rey; Otano, Jed; Echavez, Nancy; Quilab, Marina (Diksi, 2026)
Higaonon [mba], spoken by an estimated 452,000 people in north-central Mindanao, remains undocumented despite its vitality as a ‘developing language.’ The present study addresses this gap by documenting the Opol variety in Misamis Oriental through a descriptive analysis of its phonology, morphology, and syntax. Data collected from tribal leaders using elicited words and sentence lists reveal a system comprising 16 consonant phonemes, five vowels, and phonemic stress. Lexical items are categorized as open classes (nouns, verbs, adjectives and adverbs) and closed classes (pronouns, conjunctions, prepositions, and linker). In alignment with other Philippine languages, Higaonon exhibits predicate-initial word order and includes both verbal and non-verbal sentence types. By contextualizing these findings with previous orthographic work by the Komisyon sa Wikang Filipino (2023), which documented vowel variation among Higaonon communities in Bukidnon, Agusan, and Misamis Oriental, the study highlights both convergence and divergence within the language. The description of the Opol variety complements earlier orthographic observations and establishes a foundation for comparative dialectological research across Mindanao. In addition to its linguistic significance, the study supports cultural preservation, addresses prejudice against Indigenous Peoples, and serves as a resource for Mother Tongue-Based Multilingual Education (MTB-MLE).